Study on subsidence calculation model based on allometric growth of separated strata in mining overburden - Yu Guangming; Hu Xiaoyang; Lu Shibao; Song Chuanwang; Li Bingbing (Федеральное государственное автономное образовательное учреждение высшего образования «Дальневосточный федеральный университет», 2016)
In the sedimentary coal stratum, rock stratum exhibits layered feature and has a obvious level, after the underground coal mining, overlying rock often produces separation strata along the level. However, due to the difference in the layers of rocks, the change of the mining process, the difference height in the level and such factors, the rule of separated strata is extremely complex. Therefore, in this paper, by means of experiment and simulation study found that allometric phenomenon, features and rule of separated strata in mining overburden, the research reveals the mechanical mechanism of allometric development of overburden separated strata, to establish its development formula based on the theory of beam in the mechanics, analyzing the space-time law of mining subsidence and overburden separated strata, to find the relationship between surface subsidence and allometric growth of separated strata in mining overburden, to establish the subsidence model based on allometric growth of separated strata in mining overburden.
Keywords: SEPARATED STRATA IN MINING OVERBURDEN; ALLOMETRIC GROWTH; SURFACE SUBSIDENCE; CALCULATION MODEL; РАЗДЕЛЕННЫЕ СЛОИ ПРИ ВСКРЫШНЫХ РАБОТАХ; АЛЛОМЕТРИЧЕСКИЙ РОСТ; ОСЕДАНИЕ ПОВЕРХНОСТНЫХ ГРУНТОВ; РАСЧЕТНАЯ МОДЕЛЬ; 539.3